Evaluation of depression, anxiety and quality of life in hepatitis C patients who treated with direct acting antiviral agents - Kesen, Oğuzhan; Kani, Haluk Tarık; Yanartaş, Ömer; Aykut, Umut Emre; Gök, Bedin; Gündüz, Feyza; Yılmaz, Yusuf; Özdoğan, Osman Cavit; Özen Alahdab, Yeşim (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Hepatitis C virus (HCV) infection is known to impair the quality of life (QoL). Increased levels of anxiety and depression have been found in HCV infection with a prevalence of 28% and 33%, respectively. Our aim was to investigate depression, anxiety, and QoL of chronic hepatitis C (CHC) patients before and after treatment with a direct-acting antiviral agent (DAAA).Materials and Methods: In this study, enrolled CHC patients who had undergone DAAA treatment in our out-patient clinic. We administered the Hospital Anxiety and Depression (HAD) questionnaire to measure the severity of the anxiety and depression symptoms and the Short Form-36 (SF-36) questionnaire to measure the QoL at the beginning and at the end of the treatment.Results: Pretreatment anxiety and depression scores showed a statistically significant difference from the post treatment scores (p=0.000 and p=0.029 respectively). When we compared the SF-36 subitems before and after the treatment, a statistical significance was found in physical functioning (p=0.026), physical role limitation (p=0.009), bodily pain (p=0.011), general health (p=0.017), social functioning (p=0.006), and emotional role limitation (p=0.007). Also, an improvement was seen in the vitality (p=0.488) and mental health (p=0.714), which was not statistically significant.Conclusion: Depression got minimally worse in the male group despite an improvement in CHC. Anxiety scores were improved with treatment in the cirrhotic and non-cirrhotic groups significantly. A decrease in anticipatory anxiety may be related to the high treatment success with DAAA. Nearly all the subitems of the QoL scores were improved after treatment and these were more common in the female group. Elimination of HCV may itself decrease the number of patients who need psychiatric treatment.